Diagnostic and prognostic potential of miR-21, miR-29c, miR-148 and miR-203 in adenocarcinoma and squamous cell carcinoma of esophagus - Hezova, Renata; Kovarikova, Alena; Srovnal, Josef; Zemanova, Milada; Harustiak, Tomas; Ehrmann, Jiri; Hajduch, Marian; Svoboda, Marek; Sachlova, Milana; Slaby, Ondrej (Diagnostic pathology, 2015)
BACKGROUND: Esophageal cancer is the malignant tumor with very poor prognosis and increasing incidence often diagnosed at very late stage, so the prognosis of affected patients is unsatisfactory, despite the development of therapeutic option such as surgery, chemotherapy and radiotherapy. Consequently, there is a great need for biomarkers to allow a tailored multimodality approach with increased efficiency. Altered expression of microRNAs has been reported in wide range of malignancies, including esophageal cancer. The aim of this study was to examine the expression levels of candidate microRNAs in esophageal cancer and evaluate their diagnostic and prognostic potential. FINDINGS: Using quantitative real-time PCR, expression levels of 9 candidate microRNAs were examined in 62 tissue samples, 23 esophageal adenocarcinomas, 22 esophageal squamous cell carcinomas and 17 adjacent esophageal mucosa samples. MicroRNA expression levels were further analyzed in regards to clinico-pathological features of esophageal cancer patients. We observed significantly decreased levels of miR-203 and increased levels of miR-21 in adenocarcinoma tissues when compared to normal mucosa. MiR-29c and miR-148 indicated good ability to distinguish between histological subtypes of esophageal cancer. MiR-203 and miR-148 were linked to disease-free survival and overall survival in esophageal adenocarcinoma patients, and miR-148 also in esophageal squamous cell carcinoma patients. CONCLUSIONS: Our data suggest that altered expression of miR-21, miR-29c, miR-148 and miR-203 are related to neoplastic transformation and progression of the disease and these microRNAs could serve as a potential diagnostic and prognostic biomarkers in esophageal cancer. VIRTUAL SLIDES: The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/4646922201567057.
Keywords: regulace genové exprese u nádorů; nádorové biomarkery; Prognosis; mikro RNA; Biomarkers, Tumor; Humans; lidé středního věku; Middle Aged; Carcinoma, Squamous Cell; prognóza; mužské pohlaví; nádory jícnu; spinocelulární karcinom; Adenocarcinoma; skvamózní karcinom jícnu; Gene Expression Regulation, Neoplastic; Esophageal Neoplasms; ženské pohlaví; MicroRNAs; lidé; Aged; senioři; Male; adenokarcinom; Esophageal Squamous Cell Carcinoma; Female